Postoperative kinesiophobia in elderly patients with femoral neck fractures: a prospective study of psychological and social determinants - Guo, Kankai; Zhou, Ling; Zhang, Min; Hu, Xiaofang; Han, Yan; Hou, Jialu; Cheng, Jie; Shen, Xia; Wang, Qiaoqian; Zhang, Quanying (Frontiers in Psychology, 2025)
ObjectivesThis study examined the psychosocial correlates of postoperative kinesiophobia in elderly patients with femoral neck fractures, with a focus on the roles of psychological resilience and social support in mitigating movement-related fear during rehabilitation.MethodsA prospective observational study included 200 patients (≥65 years) undergoing femoral neck fracture surgery (January 2022–August 2024). Kinesiophobia was assessed using the Tampa Scale for Kinesiophobia (TSK), with scores >36 defining the kinesiophobia group (n = 120). Psychosocial factors were evaluated using the Social Support Rating Scale (SSRS), Connor-Davidson Resilience Scale (CD-RISC), General Self-Efficacy Scale (GSES), and Numeric Rating Scale (NRS) for pain. Functional independence was measured via the Functional Independence Measure (FIM). Group comparisons and logistic regression analyses identified risk factors, while Pearson correlation assessed relationships between psychosocial variables and TSK scores.ResultsThe kinesiophobia incidence was 60% (mean TSK = 39.20 ± 4.10). Key risk factors included low education (OR = 1.122), multiple comorbidities (OR = 1.312), low SSRS (OR = 1.329), low CD-RISC (OR = 1.310), severe pain (OR = 1.324), and low FIM (OR = 1.204) (all p < 0.05). SSRS and CD-RISC scores showed significant negative correlations with TSK (r = −0.524 and −0.602, respectively). The kinesiophobia group had prolonged hospitalization (10.50 ± 2.10 vs. 7.50 ± 1.80 days) and higher complication rates (6.67% vs. 1.25%).ConclusionPostoperative kinesiophobia is prevalent and strongly associated with psychosocial vulnerabilities. Interventions targeting resilience, social support, and pain management may improve rehabilitation outcomes in this high-risk population.